Cycles of Change: Understanding Corporate Employees’ Perceptions of Menstrual Leave in Delhi NCR - Nisha; Sunaina Dua; Liza Attrey; Ruchi Kaushik (NEW SOLUTIONS: A Journal of Environmental and Occupational Health Policy, 2026)
Menstrual health and hygiene management has emerged as a critical concern in workplace equity and occupational health discourse, yet policies such as menstrual leave remain contested in India. The study explores the perceptions of corporate employees in Delhi NCR on menstrual leave policy. A descriptive study was conducted with 50 corporate employees (40 women, 10 men) in Delhi NCR, selected through purposive and snowball sampling. Data were gathered using gender-specific semistructured interviews and analyzed through frequency distributions and thematic analysis. Findings suggest varying levels of awareness among women but significant information gaps among men, alongside a near-absence of formal workplace policies. Despite this, a majority endorsed menstrual leave, citing enhanced comfort, performance, and inclusivity, while concerns centered on productivity, misuse, and reinforcement of gender stereotypes. The study argues that effective policy adoption requires more than provision; it necessitates cultural change, sensitization, and systemic support to normalize menstrual health and foster inclusive workplaces.